Complementary effects of bevacizumab and MMC in the improvement of surgical outcome after glaucoma filtration surgery. (18th May 2015) - Van Bergen, Tine; Vandewalle, Evelien; Moons, Lieve; Stalmans, Ingeborg
Abstract Purpose To determine the optimum administration route of bevacizumab after glaucoma filtering surgery (GFS) and to investigate whether a reduced dose of mitomycin‐C (MMC) in combination with bevacizumab could improve surgical outcome with a reduced incidence of side‐effects. Methods Plasma levels of bevacizumab were determined via ELISA after intracameral (IC), subconjunctival (SC) and intravitreal (IV) injections in mice, subjected to a mouse model of GFS. Application of MMC was compared to bevacizumab (SC, 25 μg) and to the combined use of both adjuvants. Surgical sponges soaked in MMC 0.02% or 0.01% were exposed to the sclera for 1 or 2 min. Treatment outcome was studied by bleb investigation. Results The three administration routes of bevacizumab equally improved surgical outcome. The VEGF antibody was detected at relatively high levels in plasma shortly after IV injection, whereas it was minimally absorbed after IC and SC injections. Both bevacizumab (SC) and MMC 0.02% (2 min) similarly increased bleb area. As compared to MMC, the combined injection with bevacizumab induced an additional effect on surgical outcome. Exposure of MMC 0.02% for 1 or 2 min together with bevacizumab equally improved surgical outcome, but 2 min application induced corneal toxicity. The combined use of bevacizumab and 1‐min MMC 0.01% also improved surgical outcome compared to monotherapy, although to a lesser extent than the combination with 1‐min MMC 0.02%. Conclusions Adjunctive bevacizumab not only enhances the beneficial effect of MMC on surgical outcome, but also allows reducing the administration time of MMC 0.02%, thereby eliminating its toxic effects on the cornea.